The Effectiveness of Internet-Based Supervision on The Covid 19 Pandemic Situation - Happy Fitria; Syarwani Ahmad; Dewi Novita (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The background of this research starts from the current state and situation in the world. The coronavirus epidemic (Covid-19) was determined as a public health emergency that is troubling the world and the virus has now spread to various countries. Today's children and youth are global citizens, powerful drivers of change and members of future generations. Every crisis that occurs is an opportunity to help them learn, the most important is the protection of children and educational facilities. The impact of this situation has had a profound influence on the world of education. In the field of education, applying technology as an online educational tool that can be accessed by students. The progress and role of technology has been so prominent that the use of media and supervision has begun to be adjusted to progress. In the field of education supervision there are still obstacles and this can be overcome by utilizing an online-based supervision program. This research is a descriptive qualitative research with data collection techniques in the form of observation, documentation and interviews. This research was conducted at MAN 1 Musi Banyuasin. The results of this study indicate the supervisory competence of madrasah principals in monitoring the implementation of online learning in a covid-19 pandemic situation.